2021
DOI: 10.1186/s40168-021-01158-y
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial growth and volatile organic compound (VOC) emissions from carpet and drywall under elevated relative humidity conditions

Abstract: Background Microbes can grow in indoor environments if moisture is available, and we need an improved understanding of how this growth contributes to emissions of microbial volatile organic compounds (mVOCs). The goal of this study was to measure how moisture levels, building material type, collection site, and microbial species composition impact microbial growth and emissions of mVOCs. We subjected two common building materials, drywall, and carpet, to treatments with varying moisture availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…corroborated the associative link between microbial exposure and allergic reactions. Additional exacerbating factors like high ambient humidity and inadequate ventilation further compound these risks, as corroborated by studies from Haines et al [9] and Onmek et al [10].…”
Section: Introductionmentioning
confidence: 79%
“…corroborated the associative link between microbial exposure and allergic reactions. Additional exacerbating factors like high ambient humidity and inadequate ventilation further compound these risks, as corroborated by studies from Haines et al [9] and Onmek et al [10].…”
Section: Introductionmentioning
confidence: 79%
“…Other traditional methods and techniques 4 , 6 , 17 , 43 47 , such as biological air and dust samplings, culture-based analysis, morphology techniques, and microbial volatile organic compound (VOC) measurements 48 51 , were used to evaluate the levels of molds and bacteria measured in indoor and outdoor environments, including residential dwellings (households), daycare centers, kindergartens, schools, and elderly care centers. However, many previous studies reported several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Next generation DNA sequencing-based tools using sequence analysis of microbes [19] have not yet been able to identify speci c species as a consistent microbial signature of dampness [20][21][22]. Solely analyzing species composition changes in response to moisture is not su cient to quantify microbial growth due to the in uence of sampling site [20,23,24].…”
Section: Introductionmentioning
confidence: 99%